TAXONOMIC COMPOSITION OF PLAGUE MICROBE HOSTS AND VECTORS WITHIN THE STAVROPOL AREA OF THE PRE-CASPIAN SANDY NATURAL PLAGUE FOCUS: CURRENT STATE - U. M. Ashibokov; P. N. Korzhov; A. A. Vetoshkin; D. B. Surkhayev; A. K. Khalidov; M. P. Grigoriev (Наука. Инновации. Технологии)
Materials and methods of research. The presented work is based on the materials of the Stavropol Anti-Plague Institute of Rospotrebnadzor, archival data of the Budennovsky PCHO of the Dagestan Anti-Plague Station of Rospotrebnadzor and the analysis of the literature. Results. Within the framework of this work, the territory of the Caspian sandy natural plague center is considered within the new borders (according to the proposals of the specialists of the Stavropol Anti-Plague Institute of Rospotrebnadzor and Rosnipchi «Microbe» of Rospotrebnadzor). A list of the fauna of terrestrial mammals, fleas and ixodid ticks - carriers and carriers of the plague microbe of the Stavropol part of the focus, in accordance with modern systematic views and new borders, has been compiled. There are 25 species of rodents, 1 species of hares, 5 species of insectivores, 10 species of predators, 33 species of fleas, 21 species of ticks. Conclusions. The taxonomic composition of carriers and vectors of the plague microbe within the Stavropol territory has been clarified.